The Practice of Using Electronic Evidence in Civil Procedure Law: Obstacles and Challenges - Fadhel Arjuna Adinda; Ema Rahmawati; Eman Suparman; John Woodward (Lex Scientia Law Review, 2026)
Law Number 1 of 2024 concerning the Second Amendment to Law Number 11 of 2008 concerning Electronic Information and Transactions has a significant impact on the regulation of Cyber Law in Indonesia, including the expansion of evidence recognized in the applicable Law of Procedure in Indonesia. The arrangement of the expansion of the evidence in procedure law provides legal certainty due to the shift in the habits of today’s society which originally survived with conventional habit turning towards digital. The applicable procedural law in Indonesia is an old legal product, including regarding the expansion of valid evidence, but often in the settlement of civil dispute, electronic evidence submitted by private parties is rejected and not even considered at all by the panel of judges examining the case. This research aims to find out how the parties and the panel of judges treat electronic evidence in the examination of evidence. The problem of this research is that there are no specific rules regarding the procedures for taking, examining, verifying and submitting electronic evidence in court. The research method used is normative legal research that uses secondary data and consist of primary, secondary and tertiary legal materials. Novelty in this research specifically discusses the vagueness of norms against the use of electronic evidence.